Associations between enteral nutrition and outcomes in the SUP‐ICU trial: Protocol for exploratory post hoc analyses. Issue 4 (25th January 2023) - Borthwick, Mark; Granholm, Anders; Marker, Søren; Krag, Mette; Lange, Theis; Wise, Matt P.; Bendel, Stepani; Keus, Frederik; Guttormsen, Anne Berit; Schefold, Joerg C.; Wetterslev, Jørn; Perner, Anders; et al.
Abstract: Critically ill patients are at risk of gastrointestinal (GI) bleeding. Counter measures to minimise this risk include the use of pharmacological stress ulcer prophylaxis (SUP). The effect of enteral nutrition as SUP on GI bleeding event rates is unknown. There are conflicting data describing the effect of co‐administration of enteral nutrition with pharmacological SUP, and there is substantial variation in practice. We aim to conduct an exploratory post hoc analysis to evaluate the association of enteral nutrition with clinically important GI bleed rates in ICU patients included in the SUP‐ICU trial, and to explore any interactions between enteral nutrition and pharmacologic SUP on patient outcomes. The SUP‐ICU trial dataset will be used to assess if enteral nutrition is associated with the outcomes of interest. Extended Cox models will be used considering relevant competing events, including treatment allocation (SUP or placebo) and enteral nutrition as a daily time‐varying covariate, with additional adjustment for severity of illness (SAPS II). Results will be presented as adjusted hazard ratios for treatment allocation and enteral nutrition, and for treatment allocation and enteral nutrition considering potential interactions with the other variable, all with 95% confidence intervals and p‐values for the tests of interaction. All results will be considered as exploratory only. This post hoc analysis may yield important insights to guide practice and inform the design of future randomised clinical trial investigating the effect of enteral nutrition on GI bleeding.